Efficient treatment for tannery wastewater through sequential electro-Fenton and electrocoagulation processes. Issue 3 (June 2022) - Rezgui, Soumaya; Ghazouani, Mouna; Bousselmi, Latifa; Akrout, Hanene
Abstract: This work aims to study the ability of using single and sequential electro-Fenton (EF) and electrocoagulation (EC) processes in order to treat tannery wastewater. The first method (EF) was run with an air diffusion cathode for H2 O2 generation and boron–doped diamond (BDD) as an anode. The second method (EC) was conducted with mild steel electrodes. The applied processes' performance was monitored by the removals of chemical oxygen demand (COD) along with the total Cr in addition to the electric energy consumption (EEC). To achieve the allowable discharge limits in aquatic media, a hybrid 2 h EF-5 h EC process was applied to treat tannery wastewater, based on the optimization results of every single method, achieving (88.1 ± 4.8)% COD removal rate with total elimination of Cr. In addition, the results of other parameters evolution such as pH, turbidity and the concentration of ions were discussed. As a result, the global EEC of the hybrid treatment was reduced to about 1.7 times. Finally, precipitate and sludge generated at the end of each treatment were examined by X-Ray Diffraction (XRD) analysis to determine their crystalline structure for valorization or reuse possibilities. Graphical Abstract: ga1 Highlights: Electrochemical 2 h EF-5 h EC hybrid process is effective for the treatment of tannery wastewater. Color and COD removals were 100% and 88%. Cr was totally removed by reduction-precipitation method during EF process. Combination avoids environmental issues related to the disposal of EC sludge.